Shopee Live as an Interactive Marketing Platform: An Influencer-Based Analysis - Wahyu Purnomo; Hendry Kurniawan (International Journal of Economic and Tourism Research, 2025)
Live commerce has emerged as a prominent digital marketing phenomenon by integrating real-time interaction, entertainment, and online transactions within a single platform. Among various live commerce features, Shopee Live has gained increasing attention as an interactive marketing platform widely utilized by social media influencers to engage audiences. This study aims to analyze how influencers strategically utilize Shopee Live to foster audience engagement, build trust, and facilitate relational communication in live streaming commerce environments. Employing a qualitative research design, this study adopts a case study approach focusing on influencer-led Shopee Live sessions. Data were collected through semi-structured interviews with influencers, non-participant observation of live streaming interactions, and analysis of recorded Shopee Live sessions and engagement indicators. The findings reveal that effective audience engagement on Shopee Live is shaped by real-time interaction, persuasive product demonstration, and influencer credibility. Influencers who actively respond to audience feedback, demonstrate products transparently, and adapt communication styles during live sessions are more likely to generate sustained engagement and trust. The study further indicates that engagement in Shopee Live extends beyond short-term transactional outcomes and reflects a relational process grounded in interactivity and authenticity. This research contributes to the literature on live commerce and influencer marketing by positioning Shopee Live as an interactive marketing platform that supports long-term audience relationships. Practically, the findings offer strategic insights for influencers and brands seeking to optimize live streaming practices in competitive e-commerce environments.